(untitled) (European Journal of Pure and Applied Mathematics, 2021)
In this paper, we introduce AC* and ACG*-type properties and then, using these conditions along with other concepts, define two Denjoy-type integrals of a function with values in a locally convex topological vector space (LCTVS). We show, among others, that these newly defined integrals are included in the SH integral, a stronger version of the Henstock integral for LCTVS-valued functions.